Identification of a potent dual-function inhibitor for hIMPDH isoforms by computer-aided drug discovery approaches - Yazdani, Meysam; Zamani, Javad; Fatemi, Seyed Safa-Ali (Frontiers in Pharmacology, 2022)
Inosine monophosphate dehydrogenase (IMPDH) is a key enzyme in de novo biosynthesis of purine nucleotides. Due to this important role, it is a great target to drug discovery for a wide range of activities, especially immunosuppressant in heart and kidney transplantation. Both human IMPDH isoforms are expressed in stimulated lymphocytes. In addition to the side effects of existing drugs, previous studies have mainly focused on the type II isoform. In this study, virtual screening and computer-aided approaches were employed to identify potential drugs with simultaneous inhibitory effects on both human IMPDH isoforms. After Re-docking, Double-step docking, and identification of virtual hits based on the PLANTS scoring function, drug-likeness and ADME-Tox assessments of the topmost ligands were performed. Following further evaluation, the best ligand was selected and, in complex with both isoforms, simulated in monomeric and tetrameric forms using molecular dynamics to evaluate its stability and binding pattern. The results showed a potential drug candidate ((S)-N-(3-hydroxy-1-(4-hydroxyphenyl) propyl)-2-(3-methyl-2,4-dioxo-3,4-dihydropyrimidin-1(2H)-yl) acetamide) with a high inhibitory effect on the two human IMPDH isoforms. This drug-like inhibitor could potentially serve as an immunosuppressant to prevent transplant rejection response by inhibiting B- and T-lymphocyte proliferation. In addition, its effect can be evaluated in various therapeutic targets in which IMPDH is known as a therapeutic target, especially in Covid-19 patients.